Influence of lower third molar anatomic position on postoperative inflammatory complications - Freudlsperger, Christian; Deiss, Timo; Bodem, Jens; Engel, Michael; Hoffmann, Jürgen (Journal of oral and maxillofacial surgery, 2012)
Purpose: Postoperative inflammatory conditions, including alveolar osteitis, surgical site infections, and abscess, are frequent complications after surgical removal of impacted mandibular third molars and multiple associated risk factors have been identified. However, few studies have evaluated the influence of extraction difficulty according to anatomic variables on postoperative inflammatory complications. Patients and Methods: A retrospective study was performed of 585 surgically removed lower third molars. All molars were classified by a difficulty score (range 3 to 10) according to the anatomic parameters. Results: For 109 third molars (19%), the extraction difficulty was rated noncomplex (score 3 to 4); for 341 (58%), moderate (score 5 to 7); and for 135 (23%), difficult (score 8 to 10). Molars rated as moderate or difficult for extraction were more often accompanied by postoperative infection than molars rated noncomplex (odds ratio 5.3 and 3.9, respectively, P < .0001). Conclusions: The results from the present study revealed a highly significant correlation between the level of difficulty for surgical removal of lower third molars (predicted by the anatomic variables) and postoperative inflammatory complications.